Social Media Customer Engagement: Studying Anchor Seller and Brand or Product’s Effect on Customer Engagement in the Context of Social Selling Livestreams and Motivators of Engagement - CHUNG, Yuk-Kwan (2020)
Background: As a newly developed industry, online social selling lives has become highly prevalent on social media and on live streaming platforms. Modern companies and brands have begun to realize that social selling is an integral part of social media marketing strategy which plays an important role if organisations want to build positive relationships and engage in positive customer interaction. In 2020, over ten million online social selling forums are held on the Internet in China. There are over 400 thousand active anchor sellers, and the watching person-time is over 50 billion (Iimedia, 2020a). Purpose: With an evident lack of related researches within this field, the author has felt motivated to conduct a study on customer engagement in social selling lives. The purpose of this study is to establish (1): To what extent can anchor sellers and brand/product affect customer engagement on a live streaming platform? (2): What are the key motivators of customer engagement on the live streaming platform? Methodology: When considering customer engagement, there are two perspectives: unidimensional perspective (van Doorn, Dolan) and multidimensional perspective (Hollebeek, Brodie and Dessart) respectively. This study adopts a multidimensional perspective as supporting background and believes customer engagement can be categorized into three dimensions, such as behavioural dimension, affective dimension and cognitive dimension. In addition, several measurement scales of customer engagement regarding the online brand community and social media platforms are applied to address the research questions in this study. It also addresses the need for testing the measurement scale in more social media contexts from previous researchers. It would also be valuable to test it in context of social selling lives. To address the two research questions, this study conducts both quantitative methods and qualitative methods. The researcher has identified two engaging objects in social selling lives: (1) anchor seller and (2) brand or product. An online survey has been designed to explore participants’ engagement with these two objects. Questions of each object are divided into three categories in accordance with three dimensions of customer engagement; behavioural, affective and cognitive. On the other hand, qualitative in-depth interview methods were used to address research question 2 where six interviewees were recruited and questions were asked in order to evaluate their understanding, reasons and motivators of engagement in social selling lives. Result and discussion: The results indicate that customers are usually more likely to engage with anchor sellers, rather than through brands or products. Furthermore, of the three engaging dimensions, customers are more likely to be affectively involved and cognitive engagement seems to have a relatively minimal effect on customers. This study concluded that there are 10 essential motivators of customer engagement in social selling lives. There are 5 motivators from anchor sellers: external image, personalities, reputation, attractive live environment/atmosphere and promoting ability. In addition, there are 5 motivators from brand or product: product meets customer needs, surprising products, online promotion discounts, trust and loyalty of brand or product and questions about brand or product. Conclusions and Implications: In terms of conclusions, the affective factor has a relative impact on customers in terms of online social selling. The motivators mentioned above can potentially facilitate customer engagement. The result implies that some anchor seller incubation companies should be able to cultivate anchor sellers based on customer’s preferences. Brands or products should clearly identify their segmentations and target audiences in the market so that products are distributed to appropriate livestreaming platforms and anchor sellers.